Human immunodeficiency virus and oral microbiota: mutual influence on the establishment of a viral gingival reservoir in individuals under antiretroviral therapy - Ramos Peña, Diana Estefania; Pillet, Sylvie; Grupioni Lourenço, Alan; Pozzetto, Bruno; Bourlet, Thomas; Motta, Ana Carolina Fragoso (Frontiers in Cellular and Infection Microbiology, 2024)
The role of the oral microbiota in the overall health and in systemic diseases has gained more importance in the recent years, mainly due to the systemic effects that are mediated by the chronic inflammation caused by oral diseases, such as periodontitis, through the microbial communities of the mouth. The chronic infection by the human immunodeficiency virus (HIV) interacts at the tissue level (e.g. gut, genital tract, brain) to create reservoirs; the modulation of the gut microbiota by HIV infection is a good example of these interactions. The purpose of the present review is to assess the state of knowledge on the oral microbiota (microbiome, mycobiome and virome) of HIV-infected patients in comparison to that of HIV-negative individuals and to discuss the reciprocal influence of HIV infection and oral microbiota in patients with periodontitis on the potential establishment of a viral gingival reservoir. The influence of different clinical and biological parameters are reviewed including age, immune and viral status, potent antiretroviral therapies, smoking, infection of the airway and viral coinfections, all factors that can modulate the oral microbiota during HIV infection. The analysis of the literature proposed in this review indicates that the comparisons of the available studies are difficult due to their great heterogeneity. However some important findings emerge: (i) the oral microbiota is less influenced than that of the gut during HIV infection, although some recurrent changes in the microbiome are identified in many studies; (ii) severe immunosuppression is correlated with altered microbiota; potent antiretroviral therapies correct partially these modifications; (iii) periodontitis constitutes a major factor of dysbiosis, which is exacerbated in HIV-infected patients; its pathogenesis can be described as a reciprocal reinforcement of the two conditions, where the local dysbiosis present in the periodontal pocket leads to inflammation, bacterial translocation and destruction of the supporting tissues, which in turn enhances an inflammatory environment that perpetuates the periodontitis cycle. With the objective of curing viral reservoirs of HIV-infected patients in the future years, it appears important to develop further researches aimed at defining whether the inflamed gingiva can serve of viral reservoir in HIV-infected patients with periodontitis.